The Efficacy of Social Media as an Online Learning Medium during the COVID-19 Period - Bernadetha Nadeak; Jitu Halomoan Lumbantoruan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
The goal of this study was to determine the efficacy of social media as an alternative to using Online Learning Media to add new knowledge and information and assist with assignments, particularly for technical matters, at Allodia Vocational High School Bekasi City during the COVID-19 pandemic, which is currently underway. This study employs a research and development strategy, with research instruments consisting of a validation questionnaire and a product attractiveness rating questionnaire delivered in the form of a Google form. The findings revealed that students' use of social media as a learning medium was quite beneficial. This could be because practically all students have social media profiles and are therefore highly familiar with them. According to the study findings, the practicality of teaching materials uploaded on social media is very possible, according to 75% of media presentation experts, 82% of material experts, and 70% of linguists. As a result, adopting social media as a learning medium throughout the COVID-19 period is highly beneficial.